ANALISIS UPAYA PENERAPAN MANAJEMEN K3 DALAM MENCEGAH KECELAKAAN KERJA DI PROYEK PEMBANGUNAN FASILITAS PENUNJANG BANDARA OLEH PT.X (Studi Kasus di Proyek Pembangunan Bandara di Jawa Tengah) - Theresia Kartika Noviastuti; Ekawati Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The construction industry is the industry with the highest accident rate due to high-risk activities. One effort to prevent work accidents is to run an OSH management system that is integrated within the company. This is based on Heinrich's domino theory which describes the relationship of management with work accidents. PT.X is one of the companies that are conducted construction of supporting facilities in one of the airports in Central Java. This study aimed to analyze efforts to implementation OSH management in preventing work accidents in Airport Facilities Support Development Project by PT.X. In this research, the design used was descriptive observational with the approach of qualitative analysis. Research subjects were 5 people consisting of 3 main informants and 2 informants triangulation. Occupational Safety and Health Policy had been implemented but not yet optimally, The P2K3 organization had been formed but only the fulfillment of the law had not run optimally and have no effect on the workers, Occupational safety and health communication and information had running but some had not run on schedule but had been effective to the workers. Training had been done but not suitable as prevention of works accidents. Oversight of the government was still lacking and lack of resources from PT. X to exercise oversight due to a large number of workers. Companies should socialize P2K3, run Reward system, increase the number of Safety Officer, and for government service was expected to optimize supervision in the regional project area.